Kajian Pustaka Analisis Penetapan Kadar Asam Traneksamat dalam Sediaan Farmasi - Suci Puji Lestari; Hilda Aprilia; Farendina Suarantika (UNISBA Press, 2024)
Absract. Tranexamic acid is a biologically active compound with antifibrinolytic effects. This drug reversibly blocks the lysine binding site on plasminogen through the formation of a reversible complex of the drug with the plasminogen molecule thereby interfering with the action of plasmin and preventing the dissolution of the fibrin clot. The method used in this research is literature review with materials using reference articles regarding the analysis of determining levels of tranexamic acid in pharmaceutical preparations. The data used is accessed through Science Direct, Pubmed, and journals published nationally and internationally. The HPLC method with the best composition found was a mixture of 0.1 M ammonium acetate and acetonitrile in a ratio of 75:25 (v/v), with a C-18 column as the stationary phase and a flow rate of 1 mL/minute. showed good performance in the determination of tranexamic acid in pharmaceutical preparation products. Optimized parameters provide accurate results, with low detection limits and good reproducibility. It can be concluded that the optimized HPLC method provides a reliable way to measure tranexamic acid levels in pharmaceutical preparations with high sensitivity and specificity. Abstrak. Asam traneksamat adalah senyawa aktif biologis dengan efek antifibrinolitik. Obat ini secara reversibel memblok tempat pengikatan lisin pada plasminogen melalui pembentukan kompleks reversibel obat dengan molekul plasminogen sehingga mengganggu kerja plasmin dan mencegah pembubaran bekuan fibrin. Metode yang digunakan dalam penelitian ini adalah kajian pustaka dengan bahan menggunakan referensi artikel mengenai analisis penetapan kadar asam traneksamat pada sedian farmasi. Data yang digunakan diakses melalui science direct, pubmed, serta jurnal yang dipublikasikan secara nasional maupun internasional. Metode HPLC dengan komposisi terbaik yang ditemukan adalah campuran amonium asetat 0,1 M dan asetonitril dalam perbandingan 75:25 (v/v), dengan kolom C-18 sebagai fase diam dan laju aliran 1 mL/menit. menunjukkan kinerja yang baik dalam penentuan asam traneksamat dalam produk sediaan farmasi. Parameter yang dioptimalkan memberikan hasil yang akurat, dengan batas deteksi yang rendah dan reproduktifitas yang baik. Dapat disimpulkan jika metode HPLC yang telah dioptimalkan memberikan cara yang dapat dipercaya untuk mengukur kadar asam traneksamat dalam persiapan farmasi dengan sensitivitas dan spesifisitas yang tinggi.